Muscle-to-organ cross-talk mediated by interleukin 6 during exercise: a review - Sabzevari Rad, Reza; Panahzadeh, Fatemeh (Sport sciences for health, 2024)
Physical activity is increasingly recommended as a therapeutic approach for various lifestyle-related conditions, including type 2 diabetes, dementia, cardiovascular diseases, and cancer. Recent advancements in scientific research have uncovered the role of skeletal muscle as an endocrine organ, releasing interleukin 6 (IL-6) in response to physical activity. This secretion facilitates communication between the muscle and other organs/systems in the body, including the brain, adipose tissue, brown tissue, bone, liver, gut, pancreas, and within the muscle itself. IL-6 has diverse biological functions, including appetite regulation, lipid and glucose metabolism, promotion of browning of white adipose tissue, bone formation, muscle hypertrophy, and modulation of tumor growth. A search was conducted in PubMed and Web of Science from inception until December 2022 to identify original studies investigating the cross-talk mediated by Interleukin 6 during exercise. These findings suggest that IL-6 could serve as a valuable biomarker to monitor exercise prescription for individuals with conditions, such as cancer, diabetes, cardiovascular diseases, and neurodegenerative disorders.